Conservation of medicinal germplasm: a proposal to establish priorities based on conservation biology and ethnobotanical criteria - Castiñeira Latorre, Elena; Canavero , Andrés; Vidal, Rafael (Ethnobotany Research and Applications, 2023)
Background. This study focused to assess the overall status of the ex-situ collection of medicinal plant germplasm and propose management objectives based on ethnobotanical theory and conservation biology at the Germplasm Bank of the Facultad de Agronomía in Uruguay (BGFAgro). Methods. Reviewing the passport data of 3646 BGFAgro database accessions, we were able to identify 47 species with medicinal uses and pertinent historical information. A total of 37 medicinal plant species germination capacities were tested using accessions from these taxa. We used a logistic function to search the putative variations in germination capacity. To establish criteria for conservation priority, the frequency distribution of families, species, and associated uses was examined along with correspondence analysis. Results. Asteraceae and Leguminosae are the families with the highest number of medicinal species, and the years 1997 and 1998 had the highest number of conserved accessions. After 14 years of entrance into the collection, the germination values dramatically decline. There are 14 uses related to medicinal species that exhibit varying degrees of versatility, redundancy, and exclusivity. The most common uses are for the Symptoms and conditions of undefined origin and Digestive system. Conclusions. The collection needs support to reach international standards. We show a priority list of species based on ethnobotanical and conservation biology criteria as where to start to enhance ex situ and biocultural conservation tools. Keywords: Medicinal plants, germplasm banks, in situ-ex situ conservation, ethnobotanical, viability.